Progress in bio-based biodegradable polymer as the effective replacement for the engineering applicators. (15th August 2022) - Umesh, Mridul; Shanmugam, Sabarathinam; Kikas, Timo; Lan Chi, Nguyen Thuy; Pugazhendhi, Arivalagan
Abstract: The development of biopolymers has significantly touched each and every sphere of human life due to their eco friendliness and biodegradability. In recent decades, the production of biopolymers gained profound attention due to the serious environmental concerns and threat to the non-renewable resources. The increased use of synthetic plastic in biomedical and engineering applications stays as a major threat to environment when these xenobiotics enter the food chain and soil upon their careless discharge after use. The significant material properties of plastic has made it as an inevitable part in our day to day life, but the concern over the environment directs the research focus on searching and developing biopolymers and bio composites as sustainable alternatives for their synthetic counterparts. Biopolymers of commercial interest can be majorly produced intracellularly by microbes or can be extracted through chemical or biological methods from plant and animal based substrates. The potential candidates with high market value with specific reference to biomedical engineering and tissue engineering include as polyhydroxyalkanoates, cellulose, chitosan and chitin, hydroxyapatite, and pectin. Despite of having high degree of biocompatibility, the major hurdle that retracts their widespread use commercially is attributed to the cost of production. This can be tackled out by exploiting cheap raw materials like agro waste as substrate and by employing green approaches over solvent based conventional extraction methods. The reduction in the material properties of purified biopolymers restricts their widespread application especially in the fabrication of thermoplastic blends. This can be resolved by production of bio composites with improved properties than their parent biopolymers. The current review focuses on the recent developments in biopolymer science especially with regard to its application in engineering majorly biomedical and tissue engineering. This study throws light on the biosynthetic pathways, extraction methods and applications of commercially important biopolymers. Furthermore, the challenges, limitations, and future prospects in the production and commercialization of biopolymers is briefly discussed in this review.